Comforting Discomfort as Complicity: White Fragility and the Pursuit of Invulnerability. (2017) - Applebaum, Barbara
Abstract : In this article, I trouble the pedagogical practice of comforting discomfort in the social‐justice classroom. Is it possible to support white students, for instance, and not comfort them? Is it possible to support white students without recentering the emotional crisis of white students, without disregarding the needs and interests of students of color, and without reproducing the violence that students of color endure? First I address the dangers of comforting discomfort and discuss Robin DiAngelo's notion of white fragility, which has been used to explain the tendency of white people to flee discomfort rather than tarry with it (DiAngelo 2011). Employing Erinn Gilson's work on vulnerability, I argue that white fragility is not a weakness but an active performance of invulnerability (Gilson 2011; 2014). I conclude by arguing that developing vulnerability is a counter to white fragility, and that one way such vulnerability can be encouraged is through offering critical hope, which I maintain is a type of support that does not comfort.